Monopoly in the Perspective of Islamic and Conventional Law - Fahmi Irfanudin; Cahyo Setiadi Ramadhan; Denis Arifandi (ITB AAS INDONESIA Surakarta, 2022)
A nation's life is closely related to its economic activity. If the wheels of the economy do not run well, the country will stagnate, and it can even cause “death”. However, one important thing cannot be avoided in economic life, which is competition. Sometimes, it causes damage to the market because many people only want to obtain the maximum profit without ethical economic values, and one of which is the monopoly. Thus, there must be clear regulations and sanctions, and its absence may lead to conflict in the community or even causing bloodshed. Based on this background, the research reviewed monopoly according to Islamic law and conventional law. This study was qualitative research focused on literature research with the descriptive analytic method. In this case, the researcher took fiqh (Islamic law) and conventional law books with the theme of monopoly as primary data. The research data was collected and analyzed through qualitative analysis. The results showed no significant difference between monopoly law in the perspective of Islamic law and conventional law. Goods related to the public interest are prohibited from being monopolized under both laws. Accordingly, people who monopolize the goods are forced to sell their goods in order to eliminate the harm to the people who need these goods. However, the sanctions that will be given to monopolists are regulated in detail in conventional law in articles 47, 48, and 49. In contrast, the monopoly in Islam is still legal based on the texts of the Qur'an and Sunnah. Despite that, monopoly is regulated through ijtihad by considering maslahah and mafsadah with the same principle as conventional law in eliminating harm for the public